RELIGION, TECHNOLOGY AND SOCIAL CHANGE: REPRESENTATIONS OF MUSLIM WORLD IN ACADEMIC ANALYSES OF THE ROLE OF SOCIAL MEDIA IN THE ARAB SPRING - Adeela Arshad Ayaz (Universitas Islam Negeri (UIN), 2015)
This article deconstructs the dominant constructions and portrayals of the Muslim world in literature on social media and civic engagement in relation to the Arab Spring. A critical reading of literature on social media and 'Arab Spring' shows that analyses by Western scholars and commentators are still grounded in 'modernist dualism' and orientalist understandings. The article starts by tracing the history of technology to argue that analyses of social media's educational and civic potential within the Western context in general, is continuation of arguments about earlier technologies in relation to societal development. However, when it comes to analyzing social media and civic engagement particularly in the Muslim world this tendency gets muddled with another well-established trend, that of Orientalism. The overall impact of this tendency results in restricting majority of arguments within the essentialists/determinists paradigm. Such analyses essentialize the technological aspects of social media as universal and constitute the West as civilized, democratic, multicultural, and progressive. On the other hand Muslim world is represented as uncivilized, undemocratic, uncultured, and chained in past traditions. Thus, there is a need for a nuanced understanding of the relationship between the social media and civic engagement in the Muslim world, which can be conceptualized by framing the issues within a postcolonial critique of neoliberal globalization.   DOI: 10.15408/tjems.v1i2.1264